Arthroscopic Rotator Cuff Repair: Double-Row Transosseous Equivalent Suture Bridge Technique - Abdelshahed, Mina (Arthrosc Tech, 2016)
Following a failed course of conservative management, arthroscopic rotator cuff repair (ARCR) has become the gold standard treatment for patients presenting with symptomatic rotator cuff (RC) tears. Traditionally, the single-row repair technique was used. Although most patients enjoy good to excellent clinical outcomes, structural healing to bone remains problematic. As a result, orthopaedic surgeons have sought to improve outcomes with various technological and technical advancements. One such possible advancement is the double-row technique. We present a method for repairing an RC tear using double-row suture anchors in a transosseous equivalent suture bridge technique. The double-row technique is believed to more effectively re-create the anatomic footprint of the tendon, as well as increase tendon to bone surface area, and apposition for healing. However, it requires longer operating times and is costlier. This report highlights this technique for ARCR in an adult by using a double-row transosseous equivalent suture bridge.